Fixed Bed Adsorption Of Methylene Blue By Using Palm Oil Mill Effluent Waste Activated Sludge. - Kanadasan, G; M.D., Mashitah; Vadivelu, V.M.
The waste activated sludge (WAS) discharged during the aerobic treatment of palm oil mill effluent (POME) was used to produce a low cost adsorbent for the removal of methylene blue (MB) from aqueous solution.